Prevalence of tobacco use and associated factors among Injecting Drug Users and Men who have Sex with Men - Deepak Sharma; Naveen Krishan Goel; Munish Kumar Sharma; Dinesh Kumar Walia; Meenal Madhukar Thakare; Vanita Gupta; Sandeep Mittal; Manish Sharma (Wolters Kluwer Medknow Publications, 2021)
Introduction: Tobacco use is a leading cause of ill-health, disability, and death worldwide. The current study aimed at estimating the prevalence of tobacco use and identify factors associated with it among injecting drug users (IDUs) and men who have sex with men (MSM). Materials and Methods: A cross-sectional study was conducted among 100 IDUs and 100 MSM each, recruited with the help of outreach workers and peer educators of Nongovernment Organizations working for them. Tobacco usage behavior was assessed using an interviewer-administered questionnaire. Epi Info software for windows (CDC Atlanta) was used to calculate proportions and evaluate the association between tobacco use and independent variables. Results: The current tobacco use prevalence among IDUs was 91% (smokers 75%, smokeless tobacco users 45%). Similarly, the current tobacco use prevalence among MSM study participants was 48% (smokers 28%, smokeless tobacco users 32%). Around half of the current tobacco users had tried to quit tobacco in the past 12 months. Conclusions: There is a high proportion of tobacco use among both IDUs and MSM. It is therefore of utmost importance to strengthen tobacco cessation efforts in these groups.